1979
DOI: 10.1172/jci109298
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Gonadal Steroids to the Castrated Male Rat Prevents a Decrease in the Release of Gonadotropin-Releasing Hormone from the Incubated Hypothalamus

Abstract: A B S T R A C T The influence of testosterone on gonadotropin-releasing hormone (GnRH) secretion was assessed indirectly by altering the serum testosterone concentration of male rats and measuring GnRH release from their incubated hypothalami 1 wk later.GnRH release from hypothalami ofcastrated rats was 13.4±+1.2 (SE) pg/h, compared to 35.3±3.8 pg/h from hypothalami of intact rats (P < 0.001). GnRH release from the hypothalami of castrated rats treated with testosterone propionate, 100 or 500 ,ug daily, was 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Since castration also reduced the MEA content of LHRH and since the yield of granule LHRH from sham and cas trated male rats was similar (table I), it is logical to assume that the reduced capacity of the isolated granules to release LHRH is a consequence of a reduction in the amounts of LHRH available for release in the castrated animals. These findings are complementary to those of Rudenstem et al [18] who noted that the basal release of LHRH from hypo thalami of castrated male rats, incubated under in vitro con ditions, is lower than that of intact rats and that testosterone restored the release of LHRH to the level observed in the intact. The results obtained from these two experimental systems are suggestive that less LHRH is secreted from the hypothalamus of castrated than that from intact male rats.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Since castration also reduced the MEA content of LHRH and since the yield of granule LHRH from sham and cas trated male rats was similar (table I), it is logical to assume that the reduced capacity of the isolated granules to release LHRH is a consequence of a reduction in the amounts of LHRH available for release in the castrated animals. These findings are complementary to those of Rudenstem et al [18] who noted that the basal release of LHRH from hypo thalami of castrated male rats, incubated under in vitro con ditions, is lower than that of intact rats and that testosterone restored the release of LHRH to the level observed in the intact. The results obtained from these two experimental systems are suggestive that less LHRH is secreted from the hypothalamus of castrated than that from intact male rats.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, Rudenstein et al [18] reported that the basal re lease of LHRH from medial basal hypothalami of intact rats was greater than that from castrated rats. Thus, the question arises: Does castration alter the secretory function of LH RH neurons of male rats?…”
Section: Wheaton and Mccannmentioning
confidence: 85%
“…It has been demonstrated that castration is followed by a decrease of hypothalamic GnRH content [I, 30,31]. It is likely related to an increase of GnRH secretion [12] but this increase is controversial [7,26].…”
Section: Discussionmentioning
confidence: 99%
“…Sarkar et al (16) found elevated pituitary stalk plasma GnRH concentrations at the time of the proestrus LH surge in rats and the same group recently reported increased GnRH concentrations in pituitary stalk plasma 4 and 28 d following ovariectomy and adrenalectomy (17). Other studies have shown that orchidectomy reduced and subsequent testosterone or estradiol replacement restored hypothalamic GnRH content to normal in male rats (18)(19)(20). These data suggest that gonadal steroids influence either hypothalamic synthesis or release ofGnRH.…”
Section: Introductionmentioning
confidence: 91%